Aqueous extract of Platycodon grandiflorus attenuates lipopolysaccharide-induced apoptosis and inflammatory cell infiltration in mouse lungs by inhibiting PI3K/Akt signaling - Yang Zhou; Tianzi Jin; Mingtong Gao; Zichen Luo; Sadaf Mutahir; Chen Shi; Tong Xie; Lili Lin; Jianya Xu; Yingzhao Liao; Ming Chen; Haishan Deng; et al. (BMC, 2023)
Abstract Background Acute lung injury (ALI), an acute inflammatory lung disease, can cause a rapid inflammatory response in clinic, which endangers the patient's life. The components of platycodon grandiflorum, such as platycodins have a wide range of pharmacological activities such as expectorant, anti-apoptotic, anti-inflammatory, anti-tumor and anti-oxidant properties, and can be used for improving human immunity. Previous studies have shown that aqueous extract of platycodon grandiflorum (PAE) has a certain protective effect on ALI, but the main pharmacodynamic components and the mechanism of action are not clear. Methods The anti-inflammatory properties of PAE were studied using the lipopolysaccharide (LPS)-induced ALI animal model. Hematoxylin and eosin stains were used to assess the degree of acute lung damage. Changes in RNA levels of pro-inflammatory cytokines in the lungs were measured using quantitative RT-qPCR. The potential molecular mechanism of PAE preventing ALI was predicted by lipidomics and network pharmacology. To examine the anti-apoptotic effects of PAE, TdT-mediated dUTP nick-end labelling (TUNEL) was employed to determine apoptosis-related variables. The amounts of critical pathway proteins and apoptosis-related proteins were measured using Western blotting. Results Twenty-six chemical components from the PAE were identified, and their related pathways were obtained by the network pharmacology. Combined with the analysis of network pharmacology and literature, it was found that the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (AKT) signaling pathway is related to ALI. The results of lipidomics show that PAE alleviates ALI via regulating lung lipids especially phosphatidylinositol (PI). Finally, the methods of molecular biology were used to verify the mechanism of PAE. It can be found that PAE attenuates the inflammatory response to ALI by inhibiting apoptosis through PI3K/Akt signaling pathway. Conclusion The study revealed that the PAE attenuates lipopolysaccharide-induced apoptosis and inflammatory cell infiltration in mouse lungs by inhibiting PI3K/Akt signaling. Furthermore, our findings provide a novel strategy for the application of PAE as a potential agent for preventing patients with ALI.